HAVERHILL, MUNICIPAL REGISTER OF THE CITY, ch. 41, §§ 1-3 (F. P. Stiles 1897) (Passed 1896). - (:unkn) unknown (General Publisher, 1896)
The Board of Aldermen may grant a license to any suitable person to keep a shooting-gallery under such conditions and restrictions as it may deem proper, and may revoke the same at pleasure. Sect. 2. No person shall keep or suffer to be kept a shooting-gallery in a house, building, yard, or dependency thereof, by him actually occupied or owned, without such a license. Sect. 3. Any constable or member of the police force shall at all times have the right to enter upon premises occupied as a shooting-gallery for the purpose of inspection, and no person shall hinder or obstruct the entrance of such officer.
--
Keywords: SHOOTING RANGES OR GALLERIES